Development of raster scanning IMRT using a robotic radiosurgery system. (18th January 2021) - Shiomi, Hiroya; Akino, Yuichi; Sumida, Iori; Masai, Norihisa; Oh, Ryoong-Jin; Ogawa, Kazuhiko
Abstract: Treatment time with the CyberKnife frameless radiosurgery system is prolonged due to the motion of the robotic arm. We have developed a novel scanning irradiation method to reduce treatment time. We generated treatment plans mimicking eight-field intensity-modulated radiotherapy (IMRT) plans generated for the Novalis radiosurgery system. 2D dose planes were generated with multiple static beam spots collimated by a fixed circular cone. The weights of the uniformly distributed beam spots in each dose plane were optimized using the attraction–repulsion model. The beam spots were converted to the scanning speed to generate the raster scanning plan. To shorten treatment time, we also developed a hybrid scanning method which combines static beams with larger cone sizes and the raster scanning method. Differences between the Novalis and the scanning plan's dose planes were evaluated with the criterion of a 5% dose difference. The mean passing rates of three cases were > 85% for cone sizes ≤ 12.5 mm. Although the total monitor units (MU) increased for smaller cone sizes in an inverse-square manner, the hybrid scanning method greatly reduced the total MU, while maintaining dose distributions comparable to those with the Novalis plan. The estimated treatment time of the hybrid scanning with a 12.5 mm cone size was on average 22% shorter than that of the sequential plans. This technique will be useful in allowing the CyberKnife with conventional circular cones to achieve excellent dose distribution with a shortened treatment time.